Influence of the color of semi-funnel traps on Xylophagous coleoptera capture efficiency in forest fragments (Bioscience Journal, 2021)
Bark and ambrosia beetles, mainly the ones belonging to groups Scolytinae, Bostrichidae and Platypodinae, can kill trees from reforestation areas or native forests and damage the wood. Population monitoring and the identification of quarantine species are carried out by assembling ethanol-baited traps. The aims of the current study are to evaluate the influence of the color of ethanol-baited traps on the efficient capture of these insects, as well as to measure changes in colorimetric variables based on trap exposure in the field and to investigate whether these changes affect capture efficiency. Eight ethanolic traps (red, yellow, black and transparent traps - two of each color) were installed in a forest fragment in the first experimental stage – samples were collected on a weekly basis, for 11 months. New and used transparent traps were installed in the field in the second experimental stage - samples were collected for additional 11 months. A portable spectrophotometer was used to measure the colorimetric variables in these traps. The mean number of Scolytinae individuals (± SD) captured in transparent traps (48±50) was significantly higher than that of individuals captured in black (24±25), yellow (23±21) and red (22±21) traps. However, transparent traps subjected to field conditions were colonized by such as fungi, bacteria and mosses, which changed the transparent state of the traps into a darkened color and significantly affected their capture efficiency. The total number of 6,268 Scolytinae individuals were collected at this experimental stage: 4,977 of them were captured in new traps, whereas 1,291 were captured in the old ones.  Based on the herein measured colorimetric variables, such color change got significantly intensified as transparent traps remained under field conditions. In conclusion, transparent traps were more efficient in capturing Scolytinae individuals than the black, yellow and red traps. In addition, the exposure to field conditions has progressively changed equipment color and decreased its capture efficiency.